Prevalence and associated factors of neurodevelopmental disability among infants in eastern Uganda: a population based study - Gertrude Namazzi; Helena Hildenwall; Paul Mubiri; Claudia Hanson; Christine Nalwadda; Margaret Nampijja; Angelina Kakooza-Mwesige; Peter Waiswa; James K. Tumwine (BMC, 2019)
Abstract Background Neurodevelopmental disability (NDD) is increasingly acknowledged as one of the important causes of disease burden in low income countries. None the less, there is a dearth of data on the burden of NDD and its determinants in these settings. We aimed to establish the prevalence and factors associated with NDD among infants in Eastern Uganda. Methods We assessed 487 infants aged 9-12 months within Iganga-Mayuge Health Demographic Surveillance Site in Eastern Uganda using the Malawi Developmental Assessment Tool. The tool has four domains: gross motor, fine motor, language and social domains. An infant failed a domain if she/he failed more than two parameters of the expected at his/her age. We interviewed mothers on factors that could influence the infants' neurodevelopmental outcomes. Data were analysed using STATA version 14. We used odds ratios and 95% confidence intervals to assess statistical significance of associations. Results Of the 487 infants, 62(12.7%) had an NDD in at least one of the domains. The most affected was social behaviour where 52(10.7%) infants had an NDD. Severe impairment was seen among 9(1.8%) infants with NDD in either three or four domains. Factors associated with NDD at multivariate logistic regression included: parity of more than three children (aOR = 1.8, 95% CI: 1.02-3.18); failure to cry at birth (aOR = 3.6, 95% CI: 1.46-9.17) and post-neonatal complications (aOR = 4.15, 95% CI: 1.22-14.10). Low birth weight, immediate and exclusive breast feeding were not significantly associated with NDD. Conclusion We found a high NDD burden among infants particularly in the social behaviour domain. To optimise the socio-neural development of infants, programs are needed to educate and work with families on how to engage and stimulate infants. Existing immunisation clinics and community health worker strategies provide an excellent opportunity for stemming this burden.